Pancreatic tail splenunculus: Case report and review of the literature. (2019) - Bhogal, Ricky H.; Wotherspoon, Andrew; Zerizer, I.; Khan, Aamir Z.
Highlights: Solitary pancreatic tail lesion should undergo nuclear scintigraphy to assess whether the lesion is compatible with a splenunculus. Abstract: Introduction: Mass lesions in the pancreatic tail are increasingly identified upon radiological imaging. However the diagnosis of these lesions can be challenging and impact significantly upon patient management. Presentation of case: We report a case of an intrapancreatic accessory spleen initially diagnosed as a neuroendocrine tumour of the pancreas tail following nuclear scintigraphy. Discussion: The investigation of solitary pancreatic tail lesions and the potential management paradigms are discussed. Conclusion: Solitary lesions within the pancreatic tail should have splenunculus included in the differential diagnosis.